Potret Pengaruh Budaya Organisasi Dan Beban Kerja Terhadap Kinerja Karyawan Pada Pt Dipo Internasional Pahala Otomotif Ciputat Timur Tangerang Selatan - Adinda Mutiara Pratiwi; Abdul Azis (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study is to determine the overview of organizational culture and workload on employee performance at PT Dipo International Pahala Otomotif, Ciputat Timur, South Tangerang. The sampling technique used is saturated sampling, consisting of 120 employees. Data collection techniques include both primary and secondary data. Data analysis techniques used are descriptive statistics, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t-test, and F-test. The results of the study show that:(1) Partially, there is an influence of organizational culture on employee performance at PT Dipo International Pahala Otomotif. This is proven by the simple linear regression equation Y = 9.479 + 0.587X₁ and the value of t_calculated (6.755) > t_table (1.980) with a significance level of 0.002 < 0.05. (2) Partially, there is an influence of workload on employee performance at PT Dipo International Pahala Otomotif. This is proven by the simple linear regression equation Y = 12.444 + 0.618X₂ and the value of t_calculated (11.710) > t_table (1.980) with a significance level of 0.000 < 0.05. (3) Simultaneously, there is an influence of organizational culture and workload on employee performance at PT Dipo International Pahala Otomotif. This is proven by the multiple linear regression equation Y = 8.025 + 0.171X₁ + 0.542X₂, with a coefficient of determination of 55.3%, and the value of f_calculated (72.409) > f_table (2.680) with a significance level of 0.000 < 0.05.